Hubungan Corporate Governance dan Kinerja Perusahaan - Deni Darmawati; Khomsiyah Khomsiyah; Rika Gelar Rahayu (The Indonesian Journal of Accounting Research, 2013)
This study examines the relationship between corporate governance and corporate performance. This study employs a multiple regression to test the hypothesis that corporate governance and corporate performance are positively related. The rating of corporate governance perception index (CGPI) for 2001 and 2002 by the Indonesian Institute for Corporate Governance is used to measure the corporate governance implementation, and Tobin’s q as a market performance measurement (Klapper dan Love, 2002; Black, dkk. 2003) and return on equity (ROE) as operasional performance measurement (Klapper dan Love, 2002). The analysis shows that there is a no significant relationship between corporate governance index and Tobin's q but there is a significant positive relationship between corporate governance index and return on equity. It means that corporate governance implementation affect the operational performance, but market does not respond the implementation of corporate governance immediately.